Evaluation of bioprospecting potential of epiphytic Gracilaria edulis harvested from seaweed farm in Seriwe Bay, Lombok, Indonesia - EKA SUNARWIDHI PRASEDYA; FITRIANI FITRIANI; PUTU BELLA APRILLIA SARASWATI; NIRWANA HAQIQI; WANDA QORIASMADILLAH; HIKMATURROHMI HIKMATURROHMI; SITI ZAINIAH NURHIDAYATI; PUTU EKA PASMIDI ARIATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Prasedya ES, Fitriani F, Saraswati PBA, Haqiqi N, Qoriasmadillah W, Hikmaturrohmi H, Nurhidayati SZ, Ariati PEP. 2023.  Evaluation of bioprospecting potential of epiphytic Gracilaria edulis harvested from seaweed farm in Seriwe Bay, Lombok, Indonesia. Biodiversitas 24: 5343-5351. The seaweed industry is strategically important in Indonesia, comprising over 40% of the nation's aquaculture annual production. Despite the industry's promising growth, various challenges and problems remain, including intense epiphyte infestation. Hence, investigating the economic value of these epiphytes could provide new opportunities for potential industrial applications. Epiphytic algae is commonly found growing on commercial seaweeds which causes decreased biomass and increased risk of crop failure. Information regarding these epiphytic algae remains limited. This study investigates the molecular identification of the abundant epiphytic macroalgae found in one of the largest seaweed farms in, Seriwe Bay, Lombok, Indonesia. In addition, the epiphytic bioactive activity is also evaluated for further industrial potential. Molecular identification with the mitochondrial marker COX1 identifies the epiphytic macroalgae as Gracilaria edulis (S.G.Gmel.) P.C.Silva. The Indonesian G. edulis is closely related to the G. edulis specimens from Malaysia (JQ026083.1), Philippines (KY995636.1 and KY995635.1), and Thailand (JQ026088.1). The outgroup used was the G. edulis specimen from India (KP099563.1) because it shows the most distinct relationship to the other specimens. Extracted agar of Seriwe G. edulis shows moderate yield (21%) and low gel strength (134 g/cm2). The phytochemical content analyses show that G. edulis agar has a TPC value of 3.65 ± 0.52 mg GAE/g and promising antioxidant activity (DPPH IC50 = 797.40 ± 1.50 µg/mL; ABTS IC50 = 558.40 ± 1.44 µg/mL). Further phytochemical profiling with GCMS shows various promising major constituents such as tetradecanoic acid, neophyte diene, pentadecanoic acid, and hexadecanoic acid. Therefore, the findings suggest that G. edulis displays potential applications in the functional food and cosmetic industry.